Predicting Alcohol Use Based on Parental Perception and Emotion Regulation Difficulties in Youth - Marghzari, Setayesh Sadat (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to predict alcohol use based on parental perception and emotion regulation difficulties in youth. Methods and Materials: This research was correlational in nature. The statistical population consisted of all male youths aged 18 to 25 who visited health houses and cultural centers in regions 7 and 8 of Tehran in the spring of 2025. the sample of 200 individuals was selected through purposive and non-random sampling. Data were collected using the Alcohol Use Questionnaire by Sheikh (2014), the Perceived Parenting Styles Questionnaire by McClun and Merrell (1998), and the Difficulties in Emotion Regulation Scale by Gratz and Roemer (2004). The data were analyzed using the Pearson correlation coefficient and stepwise regression analysis with SPSS version 28. Findings: The findings revealed that authoritative parenting explained 21%, authoritarian parenting 36%, permissive parenting 29%, and difficulties in emotion regulation 15% of the variance in alcohol use (p < 0.05). Conclusion: It can be concluded that a positive perception of parents as emotional supporters and behavioral guides is a fundamental prerequisite for developing emotion regulation skills. Such perceptions enable adolescents to express their emotions in a safe environment without fear of rejection or blame.